Successful Treatment of Pulmonary Hemorrhage Associated with Pediatric Tsutsugamushi Disease by Chloromycetin - Liang, Yafeng; Wang, Linxia; Ye, Xiaojiao; Wang, Min; Yan, Chunxue; Pan, Guoquan (Current Signal Transduction Therapy, 2015)
Backgroud: Tsutsugamushi disease was really uncommon in the pediatric clinical. However, it can be quite severe, those who suffer them Tsutsugamushi disease can progress to multiple organ dysfunction syndrome (MODS) and hemophagocytic syndrome (HPS). Unfortunately, there were few reports on pulmonary hemorrhage caused by tsutsugamushi disease, especially in children. Because of the nonspecific clinical presentations, it was difficult to differentiate from other diseases. The mortality would be up to 60% if inappropriate antibiotics were used. Case Presentation: We report a three-year-old girl infected with tsutsugamushi, which manifested as MODS, HPS and diffuse alveolar hemorrhage. After administation of chloromycetin, the patient’s temperature fell down to normal 2 days later and mechanical ventilation was stopped after 1 week. The patient was discharged after three weeks of treatment. Since the typical eschar of tsutsugamushi disease is mostly concealed, misdiagnosis and delay in treatment often cause severe complications. Conclusion: Chloromycetin may be an alternative antibiotic choice of treatment for severe pediatric tsutsugamushi disease, though it has toxic effects on bone marrow hematopoietic function.
Keywords: pediatric